The Effect of Customer Promotion and Income on Saving Motivation in Bank Muamalat, Case Study Bank Muamalat Branch Boalemo - Suraya Teapon; Samin Latif; Imam Mashudi (Journal of Economic, Business, and Administration (JEBA), 2021)
The research objectives are: To determine the effect of promotion and income at the Muamalat Capem Boalemo bank. This type of research used in this research is a type of quantitative research. This quantitative research approach is used by researchers because it was collected either through observation or through a questionnaire (questionnaire), then described in the form of numbers. The results of this study are from the results of the above research that promotion has no effect on the motivation to save at Bank Muamalat Boalemo Branch. Evidenced by the regression test results Promotion coefficient (X1) of -0.130. The negative coefficient value indicates that (X1) against (Y) has no positive effect. In promotion there are 4 indicators, namely advertising, sales promotion, publicity and personal selling. The results of the validity test show that all statements are valid, while the reliability test shows that the research indicators are reliable. Promotion at Bank Muamalat, Boalemo branch, has no effect because the access is too far. Then there is no cash office in the district. And the operational car is not yet owned at Bank Muamalat Capem Boalemo.